2022
DOI: 10.1117/1.nph.9.3.032211
|View full text |Cite
|
Sign up to set email alerts
|

Toward an integrative neurovascular framework for studying brain networks

Abstract: . Brain functional connectivity based on the measure of blood oxygen level-dependent (BOLD) functional magnetic resonance imaging (fMRI) signals has become one of the most widely used measurements in human neuroimaging. However, the nature of the functional networks revealed by BOLD fMRI can be ambiguous, as highlighted by a recent series of experiments that have suggested that typical resting-state networks can be replicated from purely vascular or physiologically driven BOLD signals. After going t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 248 publications
(321 reference statements)
0
5
0
Order By: Relevance
“…Both cell types are important in neurovascular coupling, as nNOS is known to impact blood flow through its vasodilatory effects [51][52][53] and it also has been shown that pericytes have a role in the regulation of blood flow [54,55]. Here, the amplitude of the BOLD signal is related to the measured FC as it influences the Signal-to-Noise Ratio (SNR) and a reduced SNR can diminish the correlation between two time series, potentially leading to lower predictions of FC [56][57][58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both cell types are important in neurovascular coupling, as nNOS is known to impact blood flow through its vasodilatory effects [51][52][53] and it also has been shown that pericytes have a role in the regulation of blood flow [54,55]. Here, the amplitude of the BOLD signal is related to the measured FC as it influences the Signal-to-Noise Ratio (SNR) and a reduced SNR can diminish the correlation between two time series, potentially leading to lower predictions of FC [56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…One approach to ascertain whether vasculature variability is intricately linked to neuronal FC or if it primarily affects the magnitude of the BOLD signal, subsequently impacting measured FC, is to explore the correlation between non-BOLD FC and VS. This kind of functional connectivity can be measured using genetically encoded calcium indicators (such as GCaMP) [59][60][61] in combination with fluorescence imaging techniques such as wide-field imaging as summarized in Guilbert et al (2022) [58]. The combination of these techniques has been used in the mouse to image cortical functional connectivity [62,63] and even simultaneously with BOLD FC [64].…”
Section: Discussionmentioning
confidence: 99%
“…SPA-fNIRS has also a great potential to understand if the fNIRS-derived functional resting-state and task-positive networks represents more resting-state physiological networks or genuine NVC-associated neuronal networks. Since the interplay between these two types of networks is currently an open research question, 140 SPA-fNIRS could possible provide novel answers to this question. In addition, the extension of the fNIRS hyperscanning approach 133 to SPA-fNIRS hyperscanning, as recently demonstrated, 135 , 136 will allow one to explore the physiological functional coupling between interacting subjects in a new way.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Guilbert et al. 4 provide a thorough review to cover the vascular and neural network interaction underlying the functional connectivity detected by resting-state fMRI. Cleppien et al.…”
mentioning
confidence: 99%
“…Ioanas et al 3 provide a focused review on the capabilities and limitations of optical/fMRI method to study neurovascular coupling (NVC) and neuronal network mapping. Guilbert et al 4 provide a thorough review to cover the vascular and neural network interaction underlying the functional connectivity detected by resting-state fMRI. Cleppien et al 5 provide a comprehensive review to introduce the OPTO-MAgnetic Integration Concept (OPTOMAIC) to extract the temporal characteristics of the BOLD response based on optically recorded neuronal signals.…”
mentioning
confidence: 99%